Research on the Press-pack IGBT with High SCSOA - LENG Guoqing; ZHAO Ge; JIN Rui; GAO Mingchao; WEN Jialiang; PAN Yan (Kongzhi Yu Xinxi Jishu)
DC breaker is one of the main equipment of HVDC system converter station. As an essential component of DC breaker, the electrical performance and reliability of the press-pack IGBT (insulated gate bipolar transistor) are particularly important. Based on the demand characteristics of DC breakers, a 3 300 V IGBT chip with high turn-off capability was developed. The chip has excellent switching characteristics, short circuit characteristics and good ruggedness, and can pass shut-off 8X Ic. It has a good compatibility with independently developed FRD chip. The IGBT module of high turn-off capability which was developed based on this chip, passed the turn-off capability test under simulated working conditions